2001
DOI: 10.1046/j.1365-2222.2001.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cigarette smoke and house dust mite allergens on inflammatory mediator release from primary cultures of human bronchial epithelial cells

Abstract: Several studies have shown that exposure to cigarette smoke and/or house dust mite (HDM) can lead to increased airway inflammation in susceptible individuals. The underlying mechanisms, however, are not defined. To investigate the interaction between cigarette smoke and HDM allergen on mediator release from primary cultures of human bronchial epithelial cells. Confluent human bronchial epithelial cell cultures were exposed to cigarette smoke in the absence or presence of HDM allergen and investigated for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
5
25
0
Order By: Relevance
“…In line with our observation, RUSZNAK et al [33] found increased inflammatory mediator release from primary in vitro cultures of human bronchial epithelial cells, after exposure to cigarette smoke and Der p allergens. BLACQUIÈ RE et al [34] examined the effect of maternal smoking during pregnancy.…”
Section: Mechanisms Of Lung Disease Ea Lanckacker Et Alsupporting
confidence: 92%
“…In line with our observation, RUSZNAK et al [33] found increased inflammatory mediator release from primary in vitro cultures of human bronchial epithelial cells, after exposure to cigarette smoke and Der p allergens. BLACQUIÈ RE et al [34] examined the effect of maternal smoking during pregnancy.…”
Section: Mechanisms Of Lung Disease Ea Lanckacker Et Alsupporting
confidence: 92%
“…Additionally, Dongari-Bagtzoglou et al [29] reported that IL-8 expression is significantly higher in PDL cells from periodontitis patients than in PDL cells from healthy controls, and the level of IL-8 is negatively related to the periodontal treatment [14]. It has also been reported that tobacco smoke could up-regulate pro-inflammatory cytokines such as IL-8 in macrophages [30] as well as bronchial [31] and alveolar [32] epithelial cells. In nicotine-stimulated neutrophils, IL-8 expression was shown to be entirely dependent on NF-κB activation, as indicated by abrogation of IL-8 production in the presence of the NF-κB inhibitor, dexamethasone [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that short-term cigarette smoke exposure results in an enhanced release of IL-8, IL-1b and sICAM-1 in epithelial cell cultures (Rusznak et al, 2001). iNOS, expressed by both macrophages and epithelial cells during inflammation, plays an important role in inflammatory reactions via the production of nitric oxide.…”
Section: Egcg Treatment Of Nhbe Inhibited Csc-induced Activation Of Imentioning
confidence: 99%